Risk posed by the Ebola epidemic to the Pacific islands: findings of a recent World Health Organization assessment - Adam T Craig; Axelle Ronsse; Kate Hardie; Boris I Pavlin; Viema Biaukula; Eric J Nilles (World Health Organization Regional Office for the Western Pacific, 2015)
Objective: To assess the public health risk posed by the ongoing Ebola virus disease (EVD) epidemic in West Africa to Pacific island countries and areas and to highlight priority risk management actions for preparedness and response. Method: The likelihood of EVD importation and the magnitude of public health impact in Pacific island countries and areas were assessed to determine overall risk. Literature about the hazard, epidemiology, exposure and contextual factors associated with EVD was collected and reviewed. Epidemiological information from the current EVD outbreak was assessed. Results: As of 11 March 2015, there have been more than 24 200 reported cases of EVD and at least 9976 deaths in six West African countries. Three EVD cases have been infected outside of the West African region, and all have epidemiological links to the outbreak in West Africa. Pacific island countries' and areas' relative geographic isolation and lack of travel or trade links between countries with transmission means that EVD importation is very unlikely. However, should a case be imported, the health and non-health consequences would be major. The capacity of Pacific island countries and areas to respond adequately varies greatly between (and within) states but in general is limited. Discussion: This risk assessment highlights the needs to enhance preparedness for EVD in the Pacific by strengthening the capacities outlined in the World Health Organization Framework for Action on Ebola. Priority areas include the ability to detect and respond to suspected EVD cases quickly, isolation and management of cases in appropriately resourced facilities and the prevention of further cases through infection prevention and control. These efforts for Ebola should enhance all-hazards public health preparedness in line with the International Health Regulations (2005).